Adsorbent Based On Coconut Fabric As A Metal Remover In Drill Well Water - Fathoni, Rif'an; Pratikawati, Hesiany Febby; Supi, Supiansyah (Universitas Mulawarman, 2023)
This study aims to determine the characteristics of coconut coir activated charcoal as adsorbent, the effect of pH and interaction time on the adsorption ability of Fe. Coconut husk was calcined at 300°C for 1 hour, then activated with ZnCl2. Characterization of coconut husk activated charcoal using Atomic Absorption Spectrophotometry method. Determination of the effect of adding coconut coir activated charcoal on Fe adsorption at various time variations, namely 30, 60, and 90 minutes. The results of the first phase of research showed that the water and ash content of coconut coir activated charcoal were 12,17% and 0,8569%, respectively. The second stage of research shows that time variation affects the adsorption ability of Fe. The results of the third phase of research indicate that the characteristic testing phase of activated charcoal can remove the smell of iron (Fe) in well water.